Application of Decision Support System For Employee’s Bonus Using Analitycal Hierarchy Process Method - Devi Yuliana; Fitri Ayu; Ibnu Mas’ud; Fuji Hidayat; Silmi Alfadri (Journal of Applied Engineering and Technological Science (JAETS), 2022)
Having the best employee selection decisions on the CV. Multi Citra Agung, the writers assisted the company employing a method by developing a waterfall system. The method was carried out through this research process by designing stages of the Unified Modeling Language (UML) system. The occurred problems found were decisions that were not as expected and the lack of an objective attitude in decision making, due to the absence of a special process for evaluating employees in awarding bonuses of Multi Citra Agung by still using conventional systems. The study was conducted to select employees who are entitled to bonuses using the Analytical Hierarchy Process (AHP) method. A multi-criteria decision making process is to determine the best choice of a number of alternatives for employee performance appraisal based on attendance, discipline, communication and employee performance. The results of this research give the best ranking of employees by displaying an assessment of 6 employees in the form of criteria, total value and information of employees who are entitled to a bonus. For employees who are entitled to get a bonus which is 1 employee who fulfills a very satisfactory level with a range of 0.28 - 0.50.